Gregorian chant - Hiley, David (Cambridge introductions to music, 2009)
Machine generated contents note: Preface; 1. Gregorian chant in the service of the church; 2. The beginnings of Roman chant; other rites and other sorts of chant; 3. Tradition and innovation in medieval chant: from the ninth to the sixteenth century; 4. Thinking about Gregorian chant in the Middle Ages, and notating it; 5. New chants for new times: from the sixteenth century to the present; Aspects of performance; Glossary